Intravitreous injection of AAV2-sFLT01 in patients with advanced neovascular age-related macular degeneration: a phase 1, open-label trial. Issue 10089 (1st July 2017) - Heier, Jeffrey S; Kherani, Saleema; Desai, Shilpa; Dugel, Pravin; Kaushal, Shalesh; Cheng, Seng H; Delacono, Cheryl; Purvis, Annie; Richards, Susan; Le-Halpere, Annaig; Connelly, John; Wadsworth, Samuel C; et al.
Summary: Background: Long-term intraocular injections of vascular endothelial growth factor (VEGF)-neutralising proteins can preserve central vision in many patients with neovascular age-related macular degeneration. We tested the safety and tolerability of a single intravitreous injection of an AAV2 vector expressing the VEGF-neutralising protein sFLT01 in patients with advanced neovascular age-related macular degeneration. Methods: This was a phase 1, open-label, dose-escalating study done at four outpatient retina clinics in the USA. Patients were assigned to each cohort in order of enrolment, with the first three patients being assigned to and completing the first cohort before filling positions in the following treatment groups. Patients aged 50 years or older with neovascular age-related macular degeneration and a baseline best-corrected visual acuity score of 20/100 or less in the study eye were enrolled in four dose-ranging cohorts (cohort 1, 2 × 10 8 vector genomes (vg); cohort 2, 2 × 10 9 vg; cohort 3, 6 × 10 9 vg; and cohort 4, 2 × 10 10 vg, n=3 per cohort) and one maximum tolerated dose cohort (cohort 5, 2 × 10 10 vg, n=7) and followed up for 52 weeks. The primary objective of the study was to assess the safety and tolerability of a single intravitreous injection of AAV2-sFLT01, through the measurement of eye-related adverse events. This trial is registered withClinicalTrials.gov, numberNCT01024998 . Findings: 19 patients with advanced neovascular age-related macular degeneration were enrolled in the study between May 18, 2010, and July 14, 2014. All patients completed the 52-week trial period. Two patients in cohort 4 (2 × 10 10 vg) experienced adverse events that were possibly study-drug related: pyrexia and intraocular inflammation that resolved with a topical steroid. Five of ten patients who received 2 × 10 10 vg had aqueous humour concentrations of sFLT01 that peaked at 32·7–112·0 ng/mL (mean 73·7 ng/mL, SD 30·5) by week 26 with a slight decrease to a mean of 53·2 ng/mL at week 52 (SD 17·1). At baseline, four of these five patients were negative for anti-AAV2 serum antibodies and the fifth had a very low titre (1:100) of anti-AAV2 antibodies, whereas four of the five non-expressers of sFLT01 had titres of 1:400 or greater. In 11 of 19 patients with intraretinal or subretinal fluid at baseline judged to be reversible, six showed substantial fluid reduction and improvement in vision, whereas five showed no fluid reduction. One patient in cohort 5 showed a large decrease in vision between weeks 26 and 52 that was not thought to be vector-related. Interpretation: Intravitreous injection of AAV2-sFLT01 seemed to be safe and well tolerated at all doses. Additional studies are needed to identify sources of variability in expression and anti-permeability activity, including the potential effect of baseline anti-AAV2 serum antibodies. Funding: Sanofi Genzyme, Framingham, MA, USA.